A Block Based Scheme using Tuned Tri-threshold Fuzzy Intensification Operators for Underwater Images - Bhadoriya, D; Gupta, R; Gupta, M (International Journal of Computer Sciences and Engineering, 2019)
Basically, the contrast and sharpness of the images captured in underwater will be significantly deteriorated and diminished caused by the less perceptibility of the image which is due to the water medium’s physical properties. In this work, improved version of a block based scheme using tuned tri-threshold fuzzy intensification operator for underwater images is proposed. First of all, background image in underwater images are detected by DCT scaling. Later then image enhancement is done by using tuned tri-threshold fuzzy intensification operator and weber’s law. Propoposed algorithm is tested on various underwater images, collected from internet and compared with original block based scheme. Experimental results show that proposed scheme is better than original block based scheme.